A rare case of successful twin pregnancy in bicorporeal septate uterus with co-existent septate cervix - Raman, Srimathy; Gururaj, Shreelakshmi; Authreya, Ashwini J.; Venkataram, Padmalatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pregnancy occurring in patients with uterine malformations need to be managed with care as they are at risk of developing adverse outcomes. Multiple pregnancies in patients with uterine abnormalities further increase the risk of complications. Due to the rarity of this problem, there are no recommendations to guide and plan the management of these patients. Delivery planning is also tricky and needs to be individualised as either mode of delivery can be associated with complications. We discuss the management of a twin pregnancy in a primigravida (conceived after ovulation induction) with Mullerian abnormality- Septate uterus with co-existent septate cervix; ESHRE type U-2B C-1.